Bird, bath, and beyond - Copperman, E. J., 1957- (Copperman, E. J., 1957- Agent to the paws., 2018)
"The second in this hilarious cozy mystery series features a woman who is a talent agent for show biz animals and discovers that she has a talent herself: solving crimes. "Admirers of old comedy sketches and anyone looking for a laugh-out-loud mystery should pick up this series launch by Copperman." --Library Journal (starred) on Dog Dish of Doom "Readers will root for Kay to be more than pals with Sam Gibson, proprietor of Cool Beans coffee house--and, of course, to keep Bruno as more than a client. [Filled with] resilient, warm, funny supporting players." --Publishers Weekly on Dog Dish of Doom "The wry, feisty heroine is a welcome addition to Copperman's troupe." --Kirkus Reviews on Dog Dish of Doom Kay Powell, theatrical agent to non-human animals, is babysitting--that is, birdsitting--her client, a parrot named Barney, on the set of his new TV show, Dead City. When the show's charismatic star is shot in his trailer between scenes, the only eyewitness to the crime is--you guessed it--Barney. And even though Kay keeps explaining that even a "talking" parrot doesn't actually converse with people, the investigators insist on interrogating the bird for information he clearly can't communicate. Suspects accumulate like birdseed, and before long it's clear the killer believes Barney might actually be able to supply useful evidence. Even Barney can't fly away from this one" --